Building Consruction Illustrated - Ching, Francis D.k (New Jersey John Wily&Sons Inc, 2014)
The book contains:1.The building Site 2.Foundation Systems.3.Floor system. 5. wall system. 6. roof System. 7. Moisture&thermal protection.8.Doors&windows.9. Special Construction.10.Finish Work.11.Meckanical&Electrical Systems.12.Notes On Materials
Includes Appendix,Bibliography and index
3
Keywords: Building; House Consruction